Composite Anodes for Secondary Magnesium Ion Batteries Prepared via Electrodeposition of Nanostructured Bismuth on Carbon Nanotube Substrates. (1st January 2015) - DiLeo, Roberta A.; Zhang, Qing; Marschilok, Amy C.; Takeuchi, Kenneth J.; Takeuchi, Esther S.
Abstract : Magnesium-ion batteries are attractive in part due to the high environmental abundance and low cost of magnesium metal. Anode materials other than Mg metal can provide access to new electrochemistries in non-corrosive Mg 2+ electrolytes. A cyclic voltammetric method for the preparation of bismuth (Bi) based anodes was developed by systematically exploring electrodeposition using a quartz crystal microbalance. Controlled deposition of Bi on carbon nanotubes substrates could be achieved, enabling the first electrochemical investigation of bismuth-carbon nanotube (Bi-CNT) composite electrodes. Quasi-reversible Mg electrochemistry of Bi-CNT composite electrodes in non-corrosive magnesium-based electrolyte was demonstrated, with an initial delivered capacity exceeding 180 mAh/g. While the initial capacities were high, significant capacity decreases were observed with repeated cycling, indicating that additional development is warranted to further optimize this system.